Marketing strategies for Egyptian university libraries - Radwa Hemida (Cybrarians Journal, 2025)
This document presents a comprehensive study on evaluating marketing strategies for central libraries in Egyptian universities. It explores the current state of these strategies, identifies challenges in their implementation, and investigates their impact on increasing engagement with library services and achieving sustainability. The research utilizes a descriptive analytical approach, gathering data through interviews and reviews of central library managers and officials. The findings reveal a disparity in marketing approaches among libraries, highlighting the need for innovative and comprehensive strategies that leverage technology and increase awareness about the importance of marketing in libraries.